EUropean REcommendations for female FERtility preservation (EU-REFER): a joint collaboration between oncologists and fertility specialists - Dolmans, Marie-Madeleine; Lambertini, Matteo; Macklon, Kirsten Tryde; Almeida Santos, Teresa; Ruiz-Casado, Ana; Borini, Andrea; Bordes, Virginie; Frith, Lucy; Van Moer, Ellen; Germeyer, Ariane (Critical reviews in oncology, hematology, 2019)
In recent years, following the improved prognosis of patients with cancer, interest and attention has grown around fertility issues in these patients. International guidelines on fertility preservation in patients with cancer recommend that physicians discuss with all patients of reproductive age (or their parents/guardians, if children) the risk of infertility arising from their cancer or its treatment. Oncofertility counselling is recommended at the earliest opportunity and prior to cancer treatment, to help patients make informed decisions on pursuing fertility preservation. Currently, however, such discussions are not being routinely held. In June 2017, an esteemed group of European oncofertility experts met to discuss current unfulfilled needs in oncofertility for female cancer patients. This expert group has produced here a number of key recommendations in order to guide oncologists, haematologists, and other involved professionals with oncofertility discussions and appropriate referrals for further fertility preservation counselling and follow-up.